2016
DOI: 10.5194/acp-16-10313-2016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of European air quality modelled by CAMx including the volatility basis set scheme

Abstract: Abstract. Four periods of EMEP (European Monitoring and Evaluation Programme) intensive measurement campaigns (June 2006, January 2007, September–October 2008 and February–March 2009) were modelled using the regional air quality model CAMx with VBS (volatility basis set) approach for the first time in Europe within the framework of the EURODELTA-III model intercomparison exercise. More detailed analysis and sensitivity tests were performed for the period of February–March 2009 and June 2006 to investigate the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
76
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(86 citation statements)
references
References 51 publications
7
76
0
3
Order By: Relevance
“…The new emission inventory was used in two CTMs (EMEP and PMCAMx) and it improved the model performance for the total OA (Denier van der . Ciarelli et al (2016) showed that allowing for evaporation of primary organic particles as available in the European emission inventories degraded the model performance for the total OA mass (further underpredicting OA, but the POA to SOA ratio was in better agreement with measurements). In the same study, on the other hand, model performance improved when a volatility distribution which implicitly accounts for missing semivolatile material (increasing POA emissions by a factor of 3) was deployed.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…The new emission inventory was used in two CTMs (EMEP and PMCAMx) and it improved the model performance for the total OA (Denier van der . Ciarelli et al (2016) showed that allowing for evaporation of primary organic particles as available in the European emission inventories degraded the model performance for the total OA mass (further underpredicting OA, but the POA to SOA ratio was in better agreement with measurements). In the same study, on the other hand, model performance improved when a volatility distribution which implicitly accounts for missing semivolatile material (increasing POA emissions by a factor of 3) was deployed.…”
Section: Introductionmentioning
confidence: 93%
“…The modelling method and input data were the same as those used in the EURODELTA III (ED III) project, described in detail in Ciarelli et al (2016). The model domain covers Europe with a horizontal resolution of 0.25 • × 0.25 • .…”
Section: Regional Modelling With Camxmentioning
confidence: 99%
See 3 more Smart Citations